DINAMIKA TUTUPAN LAHAN DAN CADANGAN KARBON: TANTANGAN BAGI RENCANA TATA RUANG - Aini, Sukma Dyah; Iskandar, Doddy Aditya (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2026)
Indonesia, as one of the countries with the largest forest cover and ranked third in biodiversity, has experienced a decline in forest ecosystem coverage. Based on periodic data from 2001 to 2022, forest cover has decreased by approximately 11%. Data from Badan Pusat Statistik indicate that deforestation reached 514,835 hectares between 2013 and 2022, with the highest rates occurring in Sumatra and Kalimantan, ranging from 200,336 to 203,713 hectares. Kalimantan, as the largest contributor to forest cover, has experienced significant deforestation of up to 14.68%. The loss of forest cover due to deforestation is a major concern, considering the critical role of forests in providing ecosystem services. These services include the provision of food and timber, climate regulation through carbon sequestration and cycling, as well as the preservation of local cultural heritage, as highlighted in studies by Ranganathan (2008), Locatelli (2016), and Potschin (2016). Therefore, this study aims to predict carbon stocks under various land cover scenarios using QGIS, ArcGIS Pro, TerrSet, and InVEST. The predicted carbon stocks will then be compared with existing spatial planning policies to assess their implications for spatial structure and land use planning.